2017
DOI: 10.1200/jco.2017.72.4138
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Noncomparative, Phase II Trial of Early Switch From Docetaxel to Cabazitaxel or Vice Versa, With Integrated Biomarker Analysis, in Men With Chemotherapy-Naïve, Metastatic, Castration-Resistant Prostate Cancer

Abstract: PurposeThe TAXYNERGY trial (ClinicalTrials.gov identifier: NCT01718353) evaluated clinical benefit from early taxane switch and circulating tumor cell (CTC) biomarkers to interrogate mechanisms of sensitivity or resistance to taxanes in men with chemotherapy-naïve, metastatic, castration-resistant prostate cancer. Patients and MethodsPatients were randomly assigned 2:1 to docetaxel or cabazitaxel. Men who did not achieve $ 30% prostate-specific antigen (PSA) decline by cycle 4 (C4) switched taxane. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 26 publications
3
71
1
1
Order By: Relevance
“…Finally, the TAXYNERGY trial recently reported that patients who did not achieve ≥30% PSA response with taxane after 12 weeks of therapy would benefit from switching to other taxane, which could serve as a prognostic marker for treatment decision-making. 69 Molecular biomarkers for disease prediction and new therapeutic targets As shown in Table 5, AR-V7, a truncated splice variant with no ligand binding domain, has become an attractive biomarker predicting the effect of ASIs. Investigators have sought to develop the methods for the quantitative assessment of this splice isoform from CTCs 59 and PBMCs.…”
Section: Cross-resistance Between Classes Of Agentsmentioning
confidence: 99%
“…Finally, the TAXYNERGY trial recently reported that patients who did not achieve ≥30% PSA response with taxane after 12 weeks of therapy would benefit from switching to other taxane, which could serve as a prognostic marker for treatment decision-making. 69 Molecular biomarkers for disease prediction and new therapeutic targets As shown in Table 5, AR-V7, a truncated splice variant with no ligand binding domain, has become an attractive biomarker predicting the effect of ASIs. Investigators have sought to develop the methods for the quantitative assessment of this splice isoform from CTCs 59 and PBMCs.…”
Section: Cross-resistance Between Classes Of Agentsmentioning
confidence: 99%
“…In our previous studies, we could not implement quantitative analysis of taxane-induced MT bundling in mCRPC patient CTCs, as MT integrity was not preserved in the CTCs isolated via the PSMA-based microfluidic device [28] . Instead, we quantified nuclear AR as a read-out of taxane clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…[24] A recent first-line chemotherapy trial (FIRSTANA) comparing docetaxel versus cabazitaxel in chemotherapy-untreated CRPC patients failed to show superiority of cabazitaxel in this setting, while a second study suggested that patients who don’t achieve an adequate initial PSA response to docetaxel might fare better if they are immediately switched to cabazitaxel. [25, 26] Thus, cabazitaxel generally remains a second-line chemotherapy option for CRPC at present, while docetaxel is the preferred first-line treatment. In addition, docetaxel added to androgen deprivation has been shown to improve survival in men with metastatic hormone-sensitive prostate cancer with higher initial disease burden, representing a reasonable standard of care for newly-diagnosed metastatic patients who are chemo-fit.…”
Section: Existing Treatmentsmentioning
confidence: 99%